인삼류(홍삼, 백삼) 제조·가공업체의 미생물 오염도 조사 - 심원보; 이채원; 최영동; 박상곤; 정명진; 김정숙; 김세리; 박기환; 정덕화; Shim, Won-Bo; Lee, Chae-Won; Choi, Young-Dong; et al. (Han'gug sigpum wi'saeng anjeonseong haghoeji, 2015)
The aim of this study was to investigate microbiological contamination levels in the manufacturing company of ginseng products (white and red ginseng). Firstly, the contamination level for ginseng and each stage ginseng were 1.8~4.9 log CFU/g (total bacteria), 1.2~3.0 log CFU/g (coliform), 0.8~4.1 log CFU/g (fungi). However, only Bacillus cereus among pathogenic bacteria was detected from a few sample. The contamination of total bacteria tended to decrease as ginseng was being processing. Therefore, that of finished products (white and red ginseng) showed the lowest contamination level among each stage ginseng sample. That of fungi decreased steadily, although the contamination of fungi has tended to increase right after ginseng was steamed. Secondly, the contamination level for working tools and facilities were $1.7{\sim}4.7log\;CFU/cm^2$ (total bacteria), $0.4{\sim}4.0log\;CFU/cm^2$ (coliform), $0.9{\sim}4.2log\;CFU/cm^2$ (fungi). Especially, washing and peeling machines were higher contamination level. Finally, the contamination level of worker who washed and steamed ginseng was higher than worker who shaped, sorted and stored ginseng. Also, Staphylococus aureus was detected at 0.2~0.7 log CFU/hand on some wokers' hands. These results showed proper heating condition (temperature and time) and tidy manufacturing facility are the most important to avoid developing any microbiological problem of Ginseng Products. 국내 최대 인삼 재배지인 충남 금산군 소재의 인삼류(백삼, 홍삼) 제조업체 3곳을 대상으로 하여 수삼, 용수 등의 원부재료와 공정별 인삼류, 그리고 작업도구, 제조설비, 작업장 환경 및 작업자 개인위생에 대해 미생물 오염도를 조사하였다. 먼저 원료수삼과 제조 공정별 인삼의 경우 일반세균은 1.8~4.9 log CFU/g, 대장균군은 1.2~3.0 log CFU/g, 곰팡이는 0.8~4.1 log CFU/g으로 검출되었고, 병원성 미생물은 일부 시료에서 B. cereus만 미미한 수준으로 검출되었다. 특히 일반세균의 경우는 공정을 거치면서 오염도가 감소되어 완제품인 백삼에서는 2.7 log CFU/g, 홍삼에서는 1.8 log CFU/g으로 검출되었고, 곰팡이의 경우 홍삼 제조과정 중 증숙 후에 오염도가 증가하였다가 이후 공정에서 다시 감소하는 것으로 확인되었다. 제조설비와 작업 도구에서는 일반세균 $1.7{\sim}4.7log\;CFU/100cm^2$, 대장균군 $0.4{\sim}4.0log\;CFU/100cm^2$, 곰팡이 $0.9{\sim}4.2log\;CFU/100cm^2$의 수준으로 검출되었으며, 흙과 이물의 잔존할 가능성이 높은 세척기와 탈피기에서 비교적 높은 수치로 검출됨을 확인하였다. 작업자의 개인위생에서는 일반작업자가 실 묶음 작업자에 비해 미생물 오염도가 대체로 높은 것으로 확인되었고, 일부 작업자의 손에서는 S. aureus가 0.2~0.7 log CFU/hand 수준으로 검출되었다. 공중낙하균은 일반세균, 대장균군, 곰팡이만 미미한 수준으로 검출되었다. 따라서 인삼류 제품의 미생물 오염을 방지하기 위해서는 인삼류의 가열 또는 건조 시 적절한 온도와 시간의 준수, 제조시설의 청결 관리가 필요할 것으로 생각된다.